Private residence, general view, 85 Brattle Street, Cambridge, Massachusetts. - Floyd, Margaret Henderson. (Tufts University. Tisch Library., 2015)
General exterior view of a house at Brattle Steet in Cambridge, Massachusetts. Constructed in 1847 by Michael Norton. One of several slides taken in this area.; Caption on image: 85 Brattle Street Cambridge, MA Michael Norton builder, 1847.; Binder Number 4. Pocket Number: 20.; Format: 35mm col. slide.; Slide created date: This date is approximate. 1970.; Apply to the DCA for access to the physical slides.